The Importance of the mTOR Regulatory Network in Chondrocyte Biology and Osteoarthritis - Elena V. Tchetina (European Medical Journal Rheumatology, 2014)
Osteoarthritis (OA) is a chronic disorder associated mainly with pain, limited range of motion, stiffness, joint inflammation, and articular cartilage (AC) destruction. Recent studies demonstrated the involvement of chondrocyte differentiation (hypertrophy) as one of the mechanisms of cartilage degradation in OA. This indicates the involvement of profound alterations in chondrocyte metabolism in the course of cartilage resorption orchestrated by principal changes in the regulation of cellular function. Mammalian target of rapamycin (mTOR) controls critical cellular processes such as growth, proliferation, and protein synthesis, and integrates extracellular signals from growth factors and hormones with amino acid availability and intracellular energy status. The importance of mTOR activity during AC destruction in OA is supported by considerable alterations in the mTOR regulatory network, involving multiple intracellular (availability of growth factors, adenosine triphosphate [ATP], and oxygen as well as autophagy) and extracellular (glucose, amino acid, lipid, and hexosamine) signals. Moreover, variable mTOR gene expression in the peripheral blood of OA patients is associated with increases in pain or synovitis, and indicates a profound metabolic dissimilarity among patients that might require differential approaches to treatment. These issues are discussed in the present review article.